2006
DOI: 10.1192/pb.30.7.254
|View full text |Cite
|
Sign up to set email alerts
|

Violence, stigma and psychiatric diagnosis: the effects of a history of violence on psychiatric diagnosis

Abstract: Aims and MethodThe aim of the study was to investigate whether psychiatrists consider that patients with schizophrenia present a greater risk of violence than patients with other forms of mental illness. Two pairs of clinical vignettes were devised. In each pair, one contained a history of violence and one did not. One vignette was mailed to each of 2000 consultant psychiatrists in the UK. Respondents were asked to give a preferred diagnosis. Rates of diagnosis of bipolar disorder, schizoaffective disorder and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 11 publications
(11 reference statements)
0
9
0
2
Order By: Relevance
“…Consequently, violence committed by some individuals with severe mental illness promotes stigmatization and rejection of all persons with severe mental illness. Stigmatization may affect diagnostic decision making and treatment (Walsh & Fahy 2002;Clark & Rowe 2006), pose barriers to recovery and integration in the community, and compromise quality of life (Link & Pelham 2006).…”
Section: Why Does It Matter?mentioning
confidence: 99%
“…Consequently, violence committed by some individuals with severe mental illness promotes stigmatization and rejection of all persons with severe mental illness. Stigmatization may affect diagnostic decision making and treatment (Walsh & Fahy 2002;Clark & Rowe 2006), pose barriers to recovery and integration in the community, and compromise quality of life (Link & Pelham 2006).…”
Section: Why Does It Matter?mentioning
confidence: 99%
“…Algunos estudios muestran además por ejemplo cómo, en el caso de psiquiatras, una historia previa de violencia en un paciente tiende a determinar más fácilmente que le diagnostiquen de esquizofrenia (78). En resumen que parecería que, en este caso, el papel positivo del contacto social -al que luego haremos referencia como factor que se asocia a menor grado de estigmatización y deseo de distancia social hacia las personas con enfermedad mental (12; 20; 66)-no funcionase en el «contacto profesional».…”
Section: I22 Características Generales De Las Actitudes Hacia Las unclassified
“…There is evidence of just such a diagnostic bias. In a vignette-based study of diagnostic decisionmaking, Clark & Rowe (2006) demonstrated that psychiatrists are more likely to diagnose schizo phrenia than bipolar disorder in a patient with a diagnostically non-specific psychosis if that person has a history of violence than if they do not. This diagnostic bias will be liable to lead to underreporting of mood disorders in violent populations, perpetuating this erroneous assumption.…”
Section: Box 1 Summary Of Research Evidencementioning
confidence: 99%